Characteristics of Single Vehicle Crashes with a Teen Driver in South Carolina, 2005–2008. (January 2019) - Shults, Ruth A.; Bergen, Gwen; Smith, Tracy J.; Cook, Larry; Kindelberger, John; West, Bethany
Highlights: Teen drivers' nonfatal crash rate per mile driven was 11 times that of adult drivers. Teens were nearly twice as likely as adults to be speeding at the time of a crash. Teen driver crashes per mile driven were highest during 9:00–11:59 pm. 90% of teen drivers were restrained at the time of a crash. Teen passengers were >5X more likely to be restrained if their driver was restrained. Abstract: Objective: Teens' crash risk is highest in the first years of independent driving. Circumstances surrounding fatal crashes have been widely documented, but less is known about factors related to nonfatal teen driver crashes. This study describes single vehicle nonfatal crashes involving the youngest teen drivers (15–17 years), compares these crashes to single vehicle nonfatal crashes among adult drivers (35–44 years) and examines factors related to nonfatal injury producing crashes for teen drivers. Methods: Police crash data linked to hospital inpatient and emergency department data for 2005–2008 from the South Carolina Crash Outcomes Data Evaluation System (CODES) were analyzed. Nonfatal, single vehicle crashes involving passenger vehicles occurring on public roadways for teen (15–17 years) drivers were compared with those for adult (35–44 years) drivers on temporal patterns and crash risk factors per licensed driver and per vehicle miles traveled. Vehicle miles traveled by age group was estimated using data from the 2009 National Household Travel Survey. Multivariable log-linear regression analysis was conducted for teen driver crashes to determine which characteristics were related to crashes resulting in a minor/moderate injury or serious injury to at least one vehicle occupant. Results: Compared with adult drivers, teen drivers in South Carolina had 2.5 times the single vehicle nonfatal crash rate per licensed driver and 11 times the rate per vehicle mile traveled. Teen drivers were nearly twice as likely to be speeding at the time of the crash compared with adult drivers. Teen driver crashes per licensed driver were highest during the afternoon hours of 3:00–5:59 pm and crashes per mile driven were highest during the nighttime hours of 9:00–11:59 pm. In 66% of the teen driver crashes, the driver was the only occupant. Crashes were twice as likely to result in serious injury when teen passengers were present than when the teen driver was alone. When teen drivers crashed while transporting teen passengers, the passengers were >5 times more likely to all be restrained if the teen driver was restrained. Crashes in which the teen driver was unrestrained were 80% more likely to result in minor/moderate injury and 6 times more likely to result in serious injury compared with crashes in which the teen driver was restrained. Conclusions: Despite the reductions in teen driver crashes associated with Graduated Driver Licensing (GDL), South Carolina's teen driver crash rates remain substantially higher than those for adult drivers. Established risk factors for fatal teen driver crashes, including restraint nonuse, transporting teen passengers, and speeding also increase the risk of nonfatal injury in single vehicle crashes. As South Carolina examines strategies to further reduce teen driver crashes and associated injuries, the state could consider updating its GDL passenger restriction to either none or one passenger <21 years and dropping the passenger restriction exemption for trips to and from school. Surveillance systems such as CODES that link crash data with health outcome data provide needed information to more fully understand the circumstances and consequences of teen driver nonfatal crashes and evaluate the effectiveness of strategies to improve teen driver safety.